2022
DOI: 10.1016/j.nicl.2022.102939
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal enhancement in multiple sclerosis and other neurological diseases: A systematic review and Meta-Analysis

Abstract: Highlights Leptomeningeal enhancement (LME) is a nonspecific imaging feature. LME can be present in neoplastic, infectious, and primary neuroinflammatory diseases. The presence of LME is associated with worse outcome measures in multiple sclerosis. We recommend the ascertainment of LME in clinical practice. Neuroinflammatory animal models can be used to investigate the pathophysiology of LME.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
(118 reference statements)
1
43
0
Order By: Relevance
“…Not included in the PSR but presented for completeness is an systematic review of MRI LM enhancement (LME) of the brain in multiple sclerosis and other neuroinflammatory diseases e-published prior to print January 2022 [945]. DLMs were not specifically included.…”
Section: Diagnostic Studies For Dlmsmentioning
confidence: 99%
“…Not included in the PSR but presented for completeness is an systematic review of MRI LM enhancement (LME) of the brain in multiple sclerosis and other neuroinflammatory diseases e-published prior to print January 2022 [945]. DLMs were not specifically included.…”
Section: Diagnostic Studies For Dlmsmentioning
confidence: 99%
“…However, recent studies showed that claudin 11, a TJ protein enriched in the arachnoid barrier, is downregulated in EAE mice ( Uchida et al, 2019 ), indicating a disruption of the arachnoid BCSFB. Increased permeability of the leptomeningeal vessels has also been shown in MRI studies in several brain disorders, including stroke, CNS infections and cerebral amyloid angiopathy ( Ineichen et al, 2022 ). Leptomeninges are now recognized as key players in the development of MS and EAE ( Pikor et al, 2015 ; Russi and Brown, 2015 ; Rua and McGavern, 2018 ; Wicken et al, 2018 ).…”
Section: Neutrophil Contribution To Meningeal Inflammationmentioning
confidence: 90%
“…The demonstration of superficial cerebral vein tortuosity contrasts with the pattern of leptomeningeal enhancement that may present in neoplastic or infectious neurological diseases. 1 The brain parenchyma was of normal signal intensity on all conventional MRI sequences without focal abnormalities.…”
Section: Descriptionmentioning
confidence: 91%